THE EFFECT OF TRANSACTIONAL LEADERSHIP STYLE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT THE OFFICE OF CAPITAL INVESTMENT AND ONE-DOOR INTEGRATED SERVICES (DPMPTSP) OF SOUTH SULAWESI PROVINCE - Andi Muhammad Ouddang; Hasmawati Hasmawati; Sugianto Sugianto (Jurnal Mahasiswa Manajemen, 2026)
The Influence of Transactional Leadership Style and Work Environment on Employee Performance at the Office of Investment and One-Stop Integrated Services (DPMPTSP) of South Sulawesi Province. supervised by Hasmawati as supervisor 1 and Sugianto as supervisor II. The purpose of this study was to determine and analyze the influence of transactional leadership style and work environment partially and simultaneously on employee performance at the office of investment and one-stop integrated services of South Sulawesi Province. This study was conducted at the office of investment and one-stop integrated services of South Sulawesi Province with 89 respondents. The data analysis used was quantitative data analyzed using multiple regression analysis tools through the Statistical Package For Social Science (SPSS) program to find out information about the influence of training and organizational culture partially and simultaneously on employee performance at the office of investment and one-stop integrated services of South Sulawesi Province. The results of this study indicate that partially and simultaneously the variables of transactional leadership style and work environment have a significant effect on employee performance. Based on the research results, it also shows that to improve the performance of employees of the South Sulawesi Province Investment and One-Stop Integrated Services Office, attention is needed to training and organizational culture.